Astrocytes Protect Against Isoflurane Neurotoxicity by Buffering pro Brain-Derived Neurotrophic Factor - Stary, Creed M. (Anesthesiology, 2015)
BACKGROUND: Isoflurane induces cell death in neurons undergoing synaptogenesis via increased production of pro-brain derived neurotrophic factor (proBDNF) and activation of post-synaptic p75 neurotrophin receptor (p75(NTR)). Astrocytes express p75(NTR) but their role in neuronal p75(NTR) mediated cell death remains unclear. We investigated whether astrocytes have the capacity to buffer increases in proBDNF and protect against isoflurane/p75(NTR) neurotoxicity. METHODS: Cell death was assessed in day-in-vitro (DIV) 7 mouse primary neuronal cultures alone or in co-culture with age-matched or DIV 21 astrocytes with propidium iodide 24 hours following 1 hour exposure to 2% isoflurane or recombinant proBDNF. Astrocyte-targeted knockdown of p75(NTR) in co-culture was achieved with small interfering RNA and astrocyte-specific transfection reagent and verified with immunofluorescence microscopy. proBDNF levels were assessed by enzyme-linked immunosorbent assay. Each experiment used 6–8 replicate cultures/condition, and was repeated at least three times. RESULTS: Exposure to isoflurane significantly (p<0.05) increased neuronal cell death in primary neuronal cultures (1.5±0.7 fold, mean±SD) but not in co-culture with DIV 7 (1.0±0.5 fold) or DIV 21 astrocytes (1.2±1.2 fold). Exogenous proBDNF dose dependently induced neuronal cell death in both primary neuronal and co-cultures, an effect enhanced by astrocyte p75(NTR) inhibition. Astrocyte-targeted p75(NTR) knockdown in co-cultures increased media proBDNF (1.2±0.1 fold) and augmented isoflurane induced neuronal cell death (3.8±3.1 fold). CONCLUSIONS: The presence of astrocytes provides protection to growing neurons by buffering elevated levels of proBDNF induced by isoflurane. These findings may hold clinical significance for the neonatal and injured brain where elevated levels of proBDNF impair neurogenesis.